Health Hazards Associated with Arthropod Infestation of Stored Products - Hubert, Jan; Stejskal, Václav; Athanassiou, Christos G; Throne, James E (Annual review of entomology, 2018)
Insects and mites are common inhabitants and accidental invaders of food, including durable commodities, and their presence can have both direct and indirect effects on human health. The most common direct effect is contamination of food with arthropod fragments and related contaminants, which may be allergenic or even carcinogenic. The most important indirect effect is that their presence can change the storage microenvironment, making durable products suitable for the rapid development of fungi and other microorganisms. Some of these fungi can produce toxins (e.g., aflatoxins) that endanger human health. Insects may actively or passively contribute to the spread of microorganisms, increasing product contamination, and they may host bacteria that have developed antibiotic resistance, contributing to their spread in food. Several species also may host, attract, or transmit tapeworms, predators, or parasitoids that may affect health. This review synthesizes research on these topics and suggests directions for future research.
Keywords: Arthropod Vectors; Food Storage; Food Parasitology; Insecta; potravinářská parazitologie; skladování potravin; Animals; Mites; členovci - vektory; Food Microbiology; hmyz; zvířata; roztoči; potravinářská mikrobiologie